Marketplace and E-WOM Acceptance Drive Zalora App Usage Decisions : Penerimaan Marketplace dan E-WOM Mendorong Keputusan Penggunaan Aplikasi Zalora - Al-Hafidz, Thariq Naufaldy; Rochmaniah, Ainur (House of Wisdom: Journal on Library and Information Sciences, 2025)
This research is an exploratory research that focuses on the marketing of goods and services traded online, or commonly called e-commerce. The purpose of this study is to analyze the effect of Marketplace Acceptance and E- WOM on the Decision to Use the Zalora Application. The method used is quantitative with data collection through online questionnaires using Google Form. The number of respondents who filled out the questionnaire was 90 people. The data analysis technique used was multiple linear regression analysis. The results of the study showed a coefficient value of 0.901 which is included in the very strong category, with an adjusted R Square value of 0.808 which means that the variability of the Decision to Use can be explained by the variables of Marketplace Acceptance and E-WOM by 80.8%. The conclusion of this study is that there is a partial or simultaneous. Highlights: Marketplace Acceptance and E-WOM explain 80.8% of Zalora app usage decisions. Strong correlation (coefficient 0.901) between variables and usage decision. Quantitative analysis based on 90 respondents using multiple linear regression. Keywords: Decision to Use, E-WOM, Marketplace Acceptance